Pengaruh Digital Marketing dalam Strategi Pemasaran Global: A Systematic Literature Review - Mahwati, Syintiya Kirani (Master of Management Diponegoro University, 2024)
The advent of the internet has a profound impact on organizations, both in terms of their operational processes and strategic decision-making. This presents favorable prospects for enterprises to establish a foothold in the digital economy. This study aims to analyze the impact of incorporating digital marketing into the marketing strategy of global companies. This study employs a systematic literature review methodology, using the resources of Science Direct, Google Scholar, and Sinta websites. The results demonstrate that digital marketing has had a substantial beneficial impact on organizations by eliminating financial limitations and offering many marketing prospects for both major and little enterprises. This study will enable future studies to get more extensive and precise findings that are relevant to global business professionals.